Peningkatan Kompetensi Akuntansi Melalui Pelatihan Sertifikasi Akuntansi - Zulpahmi, Zulpahmi; Sumardi, Sumardi; Widyanto, Bagas; Hamidah Sutilah, Wanda; Nuraini, Agustina; Aisyah Luthfiati, Nur; Hidayat, Fikri (Jurnal Pengabdian Masyarakat Nusantara (JPMN), 2023)
There are various problems that arise during the Covid-19 Pandemic. Especially the realm of education. At this time the situation began to gradually return to normal. As a result, adjustments to return to the time before the pandemic must be made as soon as possible. The PKM FEB UHAMKA team then attended with the aim of providing basic assistance and training to face Professional Certification which will be carried out by grade 11 students.